'Equally unequal or unequally equal': Adopting a substantive equality approach to gender discrimination in Nigeria. (June 2017) - Durojaye, Ebenezer; Owoeye, Yinka
The purpose of this article is to critically assess the approach of Nigerian courts to interpreting section 42 of the Constitution. This article argues that Nigerian courts are yet to develop a substantive equality approach to interpreting section 42 of the Constitution. Rather, the courts have tended to adopt the formal equality approach to interpreting the section. Analysing some decisions of the Court of Appeal and the Supreme Court, the article argues that in order to safeguard women's rights and address gender inequality in the country, Nigerian courts should lean towards substantive equality approach to the interpretation of section 42 of the Constitution. This is not only consistent with Nigeria's obligations under international law but also crucial to addressing historical imbalances between men and women in the country.